Introduction - Shahar, Ido (Islamic law and society, 2008)
Abstract In this essay, we aim at placing the articles included in this theme issue in the wider context of the field by examining two general questions: First, why has the shari'a court and its associated socio-legal arena received little scholarly attention until the 1990s? Second, why has this situation changed in the last decade? Until recently, most scholars working in Islamic legal history, social history and legal anthropology were hardly interested in the courts and their legal practices. We argue that this omission was caused by the academic traditions that shaped these three sub-disciplines and that established a division of labor between and among them. In addition, we argue that the recent spike in interest in shari'a courts in all three sub-disciplines is a result of internal criticism within each field and of broad methodological and epistemological changes in the humanities and social sciences.